On Bookrolls, Pints, and Somewhat Flat Jokes: Suet. De poetis 3. 3. 9 - Kohler, Daria (Hyperboreus, 2024)
This article explores a passage of a letter from Augustus to Horace, quoted in the vita Horatii by Suetonius as evidence of him being short and overweight (Suet. De poetis 3. 3. 9). In the letter, the emperor jokingly connects the brevity of the work he received with the physical appearance of the poet. He then suggests that Horace could even write ‘in sextariolo’, an expression that commentators have been struggling to interpret. I argue both against the literal understanding of the expression ‘in sextariolo’ as ‘on a small vase’ and the alternative suggestions seeing it as a technical term for a speciﬁc kind of bookroll. Instead, I put forward an interpretation based on the similarity between a papyrus roll of a slightly smaller height and the shape of a sextarius.